Promotion of epithelial hyperplasia by interleukin-8—CXCR axis in human prostate - Smith, Diandra K. (Prostate, 2020)
BACKGROUND: The clinical manifestation of benign prostatic hyperplasia (BPH) is causally linked to the inflammatory microenvironment and proliferation of epithelial and stromal cells in the prostate transitional zone. The CXC-chemokine interleukin-8 (IL-8) contributes to inflammation. We evaluated the expression of inflammatory cytokines in clinical specimens, primary cultures, and prostatic lineage cell lines. We investigated whether IL-8 via its receptor system (IL-8 axis) promotes BPH. METHODS: The messenger RNA and protein expression of chemokines, including components of the IL-8 axis, were measured in normal prostate (NP; n = 7) and BPH (n = 21), urine (n = 24) specimens, primary cultures, prostatic lineage epithelial cell lines (NHPrE1, BHPrE1, BPH-1), and normal prostate cells (RWPE-1). The functional role of the IL-8 axis in prostate epithelial cell growth was evaluated by CRISPR/Cas9 gene editing. The effect of a combination with two natural compounds, oleanolic acid (OA) and ursolic acid (UA), was evaluated on the expression of the IL-8 axis and epithelial cell growth. RESULTS: Among the 19 inflammatory chemokines and chemokine receptors we analyzed, levels of IL-8 and its receptors (CXCR1, CXCR2), as well as, of CXCR7, a receptor for CXCL12, were 5- to 25-fold elevated in BPH tissues when compared to NP tissues (P ≤ .001). Urinary IL-8 levels were threefold to sixfold elevated in BPH patients, but not in asymptomatic males and females with lower urinary tract symptoms (P ≤ .004). The expression of the IL-8 axis components was confined to the prostate luminal epithelial cells in both normal and BPH tissues. However, these components were elevated in BPH-1 and primary explant cultures as compared to RWPE-1, NHPrE1, and BHPrE1 cells. Knockout of CXCR7 reduced IL-8, and CXCR1 expression by 4- to 10-fold and caused greater than or equal to 50% growth inhibition in BPH-1 cells. Low-dose OA + UA combination synergistically inhibited the growth of BPH-1 and BPH primary cultures. In the combination, the drug reduction indices for UA and OA were 16.4 and 7852, respectively, demonstrating that the combination was effective in inhibiting BPH-1 growth at significantly reduced doses of UA or OA alone. CONCLUSION: The IL-8 axis is a promotor of BPH pathogenesis. Low-dose OA + UA combination inhibits BPH cell growth by inducing autophagy and reducing IL-8 axis expression in BPH-epithelial cells.